Dieta hiperlipídica promove remodelação cardíaca em modelo experimental de obesidade - Martins, Fernando; Campos, Dijon Henrique Salomé [UNESP]; Pagan, Luana Urbano [UNESP]; Martinez, Paula Felippe [UNESP]; Okoshi, Katashi [UNESP]; Okoshi, Marina Politi [UNESP]; Padovani, Carlos Roberto [UNESP]; de Souza, Albert Schiaveto; Cicogna, Antonio Carlos [UNESP]; de Oliveira-Junior, Silvio Assis (Sociedade Brasileira de Cardiologia, 2015)
Background: Although nutritional, metabolic and cardiovascular abnormalities are commonly seen in experimental studies of obesity, it is uncertain whether these effects result from the treatment or from body adiposity. Objective: To evaluate the influence of treatment and body composition on metabolic and cardiovascular aspects in rats receiving high saturated fat diet. Methods: Sixteen Wistar rats were used, distributed into two groups, the control (C) group, treated with isocaloric diet (2.93 kcal/g) and an obese (OB) group, treated with high-fat diet (3.64 kcal/g). The study period was 20 weeks. Analyses of nutritional behavior, body composition, glycemia, cholesterolemia, lipemia, systolic arterial pressure, echocardiography, and cardiac histology were performed. Results: High-fat diet associates with manifestations of obesity, accompanied by changes in glycemia, cardiomyocyte hypertrophy, and myocardial interstitial fibrosis. After adjusting for adiposity, the metabolic effects were normalized, whereas differences in morphometric changes between groups were maintained. Conclusions: It was concluded that adiposity body composition has a stronger association with metabolic disturbances in obese rodents, whereas the high-fat dietary intervention is found to be more related to cardiac morphological changes in experimental models of diet-induced obesity.
High-fat diet promotes cardiac remodeling in an experimental model of obesity
Keywords: Diet, High-Fat; Epidemiology, Experimental; Obesity; Rats; Ventricular remodeling